2012
DOI: 10.1007/s10461-012-0317-8
|View full text |Cite
|
Sign up to set email alerts
|

High Acceptability of HIV Pre-exposure Prophylaxis but Challenges in Adherence and Use: Qualitative Insights from a Phase I Trial of Intermittent and Daily PrEP in At-Risk Populations in Kenya

Abstract: This paper used qualitative methods to explore experiences of men who have sex with men and female sex workers in Nairobi and Mtwapa, Kenya, who used oral preexposure prophylaxis (PrEP) for HIV prevention as part of a four-month trial of safety, acceptability and adherence. Fifty-one of 72 volunteers who took part in a randomized, placebo-controlled, blinded trial that compared daily and intermittent dosage of PrEP underwent qualitative assessments after completing the trial. Analyses identified three themes: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
231
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(254 citation statements)
references
References 19 publications
20
231
2
1
Order By: Relevance
“…Despite documentation of variable adherence,[45], [46] PrEP's acceptability has generally been high when studied among trial participants, such as female sex workers in Kenya[50] and women in Uganda, South Africa, and the US. [51] Other studies of hypothetical use among people not participating in trials have reported willingness to use oral PrEP among young urban African American men and women,[52] although a substantial proportion (40%) of male and female emergency room patients in two New York City hospitals indicated that they were unlikely to use it.…”
Section: Interventions For Preventing Hiv Infection Among Womenmentioning
confidence: 99%
“…Despite documentation of variable adherence,[45], [46] PrEP's acceptability has generally been high when studied among trial participants, such as female sex workers in Kenya[50] and women in Uganda, South Africa, and the US. [51] Other studies of hypothetical use among people not participating in trials have reported willingness to use oral PrEP among young urban African American men and women,[52] although a substantial proportion (40%) of male and female emergency room patients in two New York City hospitals indicated that they were unlikely to use it.…”
Section: Interventions For Preventing Hiv Infection Among Womenmentioning
confidence: 99%
“…In Kenya, stigma was reported to negatively affect participants’ ability to adhere to an oral PrEP regimen [11]. Similarly, Thai participants in another oral PrEP trial feared being mistakenly identified as HIV positive and experienced stigma and relationship stress [14].…”
Section: Introductionmentioning
confidence: 99%
“…23 Another study in Kenya also found fear of stigma and susceptibility to local slander or gossip among high-risk HIV negative populations. 24 In a study of African-American young adults, participants expressed apprehension about sharing their use of PrEP within their networks for fear of being mistakenly labeled as HIV-positive or as sexually indiscriminate. 19 Liu and colleagues found that in addition to fear of being stigmatized by family and peers, potential PrEP users sensed judgment and resistance from medical providers providing PrEP.…”
mentioning
confidence: 99%